Effect of Adherence to a Mediterranean Diet and Olive Oil Intake during Pregnancy on Risk of Small for Gestational Age Infants - Martínez-Galiano, Juan Miguel (Nutrients, 2018)
To quantify the effect of a Mediterranean dietary pattern, as well as the consumption of olive oil (OO), on the risk of having a small for gestational age infants (SGA), a matched case-control study was conducted in Spain. Dietary intake during pregnancy was assessed using a validated food frequency questionnaire. Three indices were used to evaluate the adherence to Mediterranean diet (MD) (Predimed, Trichopoulou and Panagiotakos). Crude odds ratios (cOR) and adjusted odds ratios (aOR) and their 95% confidence intervals (CI) were estimated using conditional logistic regression models. Results were stratified by severity of SGA: moderate (percentiles 6–10), and severe (percentiles ≤5). For moderate, four or more points in the Predimed´s index was associated with a 41% reduction of having SGA compared with women with a score ≤3, aOR = 0.59 (95% CI 0.38–0.98); for severe, the reduction in risk was not statistically significant. Similar results were found when the other MD indexes were used. An intake of OO above 5 g/day was associated with a lower risk of SGA (aOR = 0.53, 95% CI 0.34–0.85); statistical significance was observed for moderate SGA (aOR = 0.53, 95% CI 0.30–0.96), but not for severe SGA (aOR = 0.51, 95% CI 0.24–1.07), although the magnitude of ORs were quite similar. Adherence to a MD and OO intake is associated with a reduced risk of SGA.